2009
DOI: 10.1089/ars.2009.2576
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Menopause: Does Increased Iron Affect the Health of Postmenopausal Women?

Abstract: Estrogen deficiency has been regarded as the main causative factor in menopausal symptoms and diseases. Here, we show that although estrogen decreases by 90%, a concurrent but inverse change occurs in iron levels during menopausal transition. For example, levels of serum ferritin are increased by two-to threefold from before menopause to after menopause. This observation has led us to hypothesize that, in addition to estrogen deficiency, increased iron as a result of menopause could be a risk factor affecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
128
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 142 publications
(136 citation statements)
references
References 43 publications
(50 reference statements)
6
128
2
Order By: Relevance
“…The reasons for elevated body iron burden are poorly understood in cancer patients. In light of iron metabolism in women, menopause and endogenous estrogen alteration have been postulated to physiologically account for the change of body iron mass [17,60]. Estrogen is a hormone that physiologically dictates the integrity and functions for a variety of cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The reasons for elevated body iron burden are poorly understood in cancer patients. In light of iron metabolism in women, menopause and endogenous estrogen alteration have been postulated to physiologically account for the change of body iron mass [17,60]. Estrogen is a hormone that physiologically dictates the integrity and functions for a variety of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated body iron has been documented in postmenopausal women for unclear reasons [20,52,61]. For example, a previous study identified a negative correlation between serum ferritin and estrogen level in women [17]. The mechanisms underlying the correlation between estrogen and iron metabolism is still elusive thus far.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations